2018
DOI: 10.1002/ange.201800767
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐Light‐Promoted Dearomative Fluoroalkylation of β‐Naphthols through Intermolecular Charge Transfer

Abstract: The first visible-light-promoted dearomative fluoroalkylation of b-naphthols was realized without the assistance of any transition-metal catalysts or external photosensitizers. Inexpensive fluoroalkyl iodides were directly used as efficient fluoroalkylation reagents under very mild reaction conditions. The scope of this process was found to be general and broad, and both trifluoromethyl and perfluoroalkyl groups (-C 4 F 9 , -C 6 F 13 ,a nd -C 8 F 17 )w ere installed in excellent yields.P reliminary mechanistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(2 citation statements)
references
References 109 publications
1
1
0
Order By: Relevance
“…Mixing acetonitrile (missing the iodo‐component of the reagent) with sodium ascorbate did not lead to a bathochromic shift (Figure S3) [20] . Similar bathochromic shifts have been reported in literature between iodo‐reagents and phenolates [22,26a–d] or thiophenolates [26e] . In particular, in the case of ICH 2 SO 2 Ph, Filippini, Dell'Amico and coworkers probed the EDA complex between phenol‐DBU‐ICH 2 SO 2 Ph via DFT calculations and UV‐Vis studies and suggested that halogen bonding is in place, rather than hydrogen bonding [26b] .…”
Section: Resultssupporting
confidence: 72%
“…Mixing acetonitrile (missing the iodo‐component of the reagent) with sodium ascorbate did not lead to a bathochromic shift (Figure S3) [20] . Similar bathochromic shifts have been reported in literature between iodo‐reagents and phenolates [22,26a–d] or thiophenolates [26e] . In particular, in the case of ICH 2 SO 2 Ph, Filippini, Dell'Amico and coworkers probed the EDA complex between phenol‐DBU‐ICH 2 SO 2 Ph via DFT calculations and UV‐Vis studies and suggested that halogen bonding is in place, rather than hydrogen bonding [26b] .…”
Section: Resultssupporting
confidence: 72%
“…Dearomative perfluoroalkylation of 2‐naphthols with fluoroalkyl iodides through a visible‐light‐induced intermolecular charge transfer process was realized by Wang, Xu, and co‐workers (Scheme A) . A radical chain propagation pathway was proposed for this transformation with calculated quantum yield of ϕ = 14, where visible light irradiation of EDA complex 47 , formed between deprotonated 2‐naphthol and fluoroalkyl iodide, underwent SET, generating perfluoroalkyl radical (Scheme B).…”
Section: Assisted Photoactivation Of Arenesmentioning
confidence: 99%